Staphylococcal Enterotoxins Dose-Dependently Modulate the Generation of Myeloid-Derived Suppressor Cells - Stoll, Hartmut; Ost, Michael; Singh, Anurag; Mehling, Roman; Neri, Davide; Schäfer, Iris; Velic, Ana; Macek, Boris; Kretschmer, Dorothee; Weidenmaier, Christopher; Hector, Andreas; Handgretinger, Rupert; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Staphylococcus aureus is one of the major human bacterial pathogens causing a broad spectrum of serious infections. Myeloid-derived suppressor cells (MDSC) represent an innate immune cell subset capable of regulating host-pathogen interactions, yet their role in the pathogenesis of S. aureus infections remains incompletely defined. The aim of this study was to determine the influence of different S. aureus strains and associated virulence factors on human MDSC generation. Using an in vitro MDSC generation assay we demonstrate that low concentrations of supernatants of different S. aureus strains led to an induction of functional polymorphonuclear MDSC (PMN-MDSC), whereas increased concentrations, conversely, reduced MDSC numbers. The concentration-dependent reduction of MDSC correlated with T cell proliferation and cytotoxicity. Several findings supported a role for staphylococcal enterotoxins in modulating MDSC generation. Staphylococcal enterotoxins recapitulated concentration-dependent MDSC induction and inhibition, T cell proliferation and cytotoxicity, while an enterotoxin-deficient S. aureus strain largely failed to alter MDSC. Taken together, we identified staphylococcal enterotoxins as main modulators of MDSC generation. The inhibition of MDSC generation by staphylococcal enterotoxins might represent a novel therapeutic target in S. aureus infections and beyond in non-infectious conditions, such as cancer.